PENERAPAN MEDIA PEMBELAJARAN ILMU DASAR TEKNIK MESIN PADA SEKOLAH INDONESIA DAVAO FILIPINA - Rachmad Syarifudin Hidayatullah; Wahyu Dwi Kurniawan; Soeryanto; Mochamad Cholik; Dewanto; Djoko Suwito; Yunus; Theodorus Wiyanto Wibowo; Saiful Anwar; Nur Aini Susanti; Muamar Zainur Arif; Heru Arizal; Ali Hasbi Ramadhani; Bima Anggana Widhiarta Putra (LPPM Universitas Al Muslim, 2025)
This community service activity aimed to improve the quality of basic mechanical engineering learning at Sekolah Indonesia Davao (SID) through the application of innovative and effective learning media. SID has limited access to basic mechanical engineering learning materials, and there is no media that makes it easier to understand the material. To overcome this problem, the community service activity implementation team implemented basic engineering learning media aimed for junior high and high school levels. The implementation methods included identifying partner problems, determining solutions, implementing media, monitoring, and compiling reports. The results of the implementation of this activity showed that the basic mechanical engineering learning media has been handed over to the partner on May 28, 2024, and training on how to operate the media has been carried out. This activity also received a positive response from the partner, because it made a significant contribution to improving the understanding and skills of students at SID in the field of mechanical engineering, as well as strengthening cooperation between Surabaya State University and SID in the field of education.